Leisure, sport and tourism, politics, policy and planning - Veal, Anthony James (Cambridge, Massachusetts : CABI, 2010)
This comprehensive, multi-disciplinary introduction to public policy and planning as carried out by governments and associated agencies covers the rights of the person as a citizen in terms of their needs and requirements for leisure, travel and sport, and the role of the state and market in meeting these needs. Expanded to include sport as a subject separate from leisure, this new edition of the successful Leisure and Tourism Policy and Planning also addresses the issues of climate change and global warming, which are crucial considerations for tourism planners and policymakers. It covers theoretical perspectives and practical guidelines for the application of a range of analytical techniques, and includes an extensive bibliography and questions and exercises for each chapter, making it an ideal text for students as well as practitioners.
Rev. ed. of: Leisure and tourism policy and planning. c2002.
Includes bibliographical references and index.
Keywords: Leisure -- Government policy -- Great Britain; Tourism -- Government policy -- Great Britain; Recreation -- Great Britain -- Planning